SIKAP MAHASISWA POLITEKNIK NEGERI MADURA DALAM MENERIMA INFORMASI COVID-19 DI MEDIA SOSIAL - Anggeria Oktavisa Denta; Rahayu Yuliana Watiningrum; Kembang Wilujeng Puspitasari (Universitas Nazhatut Thullab Al- Muafa Sampang, 2023)
Introduction : Attitudes in receiving Covid-19 information are different for each individual because attitudes are influenced by knowledge of the situation experienced and the possibility of a tendency to act. The purpose of this study research was to determine the attitude of Madura State Polytechnic students in receiving Covid-19 information on social media. This research was conducted from February to August 2022 Methods : This research uses descriptive statistical analysis.. The population in this research were all students (19-21 old) od Madura State were 800 people. The sample in this research were 267 students of Madura State Polytechnic. Using the non-probability clustesr sampling technique. Collecting data using a close ended likert scale questionnaire and analyzed descriptively (Mean-T) and presented in the form of tables and narratives. Result: Based on the research results, the attitude of Madura State Polytechnic students was mostly favorable, as many as 159 respondents (60%). Conclusion: The majority of Madura State Polytechnic students have a favorable attitude in receiving Covid-19 information on social media and it is hoped that students will be able to maintain choosing the correct information on social media